2016
DOI: 10.1073/pnas.1521607113
|View full text |Cite
|
Sign up to set email alerts
|

Two types of quasi-liquid layers on ice crystals are formed kinetically

Abstract: Surfaces of ice are covered with thin liquid water layers, called quasi-liquid layers (QLLs), even below their melting point (0°C), which govern a wide variety of phenomena in nature. We recently found that two types of QLL phases appear that exhibit different morphologies (droplets and thin layers) [Sazaki G. et al. (2012) Proc Natl Acad Sci USA 109(4):1052−1055]. However, revealing the thermodynamic stabilities of QLLs remains a longstanding elusive problem. Here we show that both types of QLLs are metastabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
69
1
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(74 citation statements)
references
References 42 publications
(31 reference statements)
3
69
1
1
Order By: Relevance
“…Surprisingly, this work revealed that, contrary to the common belief that QLLs completely and homogeneously wet ice surfaces, they are spatiotemporally heterogeneous and are absent in the equilibrium conditions (22,(24)(25)(26). Furthermore, we have observed that QLLs exhibit more than one wetting morphology: droplet type, thin-layer type, and their coexistence (sunny-side-up type) at supersaturation (22,(24)(25)(26). This finding fundamentally requires us to recast the conventional understanding based on spatiotemporally averaged equilibrium theories and experiments (e.g., scattering, spectroscopy, and ellipsometry), because of ignorance of the counterintuitive nature of QLLs.…”
contrasting
confidence: 89%
See 2 more Smart Citations
“…Surprisingly, this work revealed that, contrary to the common belief that QLLs completely and homogeneously wet ice surfaces, they are spatiotemporally heterogeneous and are absent in the equilibrium conditions (22,(24)(25)(26). Furthermore, we have observed that QLLs exhibit more than one wetting morphology: droplet type, thin-layer type, and their coexistence (sunny-side-up type) at supersaturation (22,(24)(25)(26). This finding fundamentally requires us to recast the conventional understanding based on spatiotemporally averaged equilibrium theories and experiments (e.g., scattering, spectroscopy, and ellipsometry), because of ignorance of the counterintuitive nature of QLLs.…”
contrasting
confidence: 89%
“…For ΔF < 0, ice surfaces lower the total free energy by ΔF by getting wet, which drives the spontaneous formation of QLLs and permits the equilibrium surface melting. However, we previously found the absence of QLLs at and near the ice-vapor equilibrium (26). As shown in Movie S4, a droplettype (partially wet) QLL gradually disappears on an ice surface at the ice-vapor equilibrium (T = −1.5 °C and p = 540 Pa) for sufficiently long time to observe the whole kinetics directly.…”
Section: Thermal Fluctuation Effects: Droplet Nucleation From Thin LImentioning
confidence: 77%
See 1 more Smart Citation
“…The study of Sánchez et al (4) does not provide insight into what happens above 257 K, so it is unclear whether melting continues in a bilayer-by-bilayer manner beyond the single step postulated at 257 K. However, much closer to the bulk melting temperature a complementary series of high-resolution optical interferometry measurements has provided insight (16,17).…”
mentioning
confidence: 99%
“…For example, Kunitake and co-workers introduced hydrophilic oligoethylene glycol bis-acrylate molecules in the interlayer spaces of a synthetic multilayered double-alkyl cationic lipid templates (Figure 3). 53,54 Crosslinking polymerization within the template nanospaces upon the irradiation of an ultrahigh pressure Hg lamp in the presence of a photoinitiator resulted in highly oriented hybrids. Extracting the template components by immersing the hybrid film in methanol led to the formation of self-standing transparent films within which 2 nm thick 2D polymer nanosheets are stacked together.…”
Section: Introductionsmentioning
confidence: 99%